Loss of function in ROBO1 is associated with tetralogy of Fallot and septal defects - Paul Kruszka (2018)
© Article author(s) (or their employer(s) unless otherwise stated in the text of the article) 2017. All rights reserved. No commercial use is permitted unless otherwise expressly granted. Background Congenital heart disease (CHD) is a common birth defect affecting approximately 1% of newborns. Great progress has been made in elucidating the genetic aetiology of CHD with advances in genomic technology, which we leveraged in recovering a new pathway affecting heart development in humans previously known to affect heart development in an animal model. Methods Four hundred and sixteen individuals from Thailand and the USA diagnosed with CHD and/or congenital diaphragmatic hernia were evaluated with chromosomal microarray and whole exome sequencing. The DECIPHER Consortium and medical literature were searched for additional patients. Murine hearts from ENU-induced mouse mutants and transgenic mice were evaluated using both episcopic confocal histopathology and troponin I stained sections. Results Loss of function ROBO1 variants were identified in three families; each proband had a ventricular septal defect, and one proband had tetralogy of Fallot. Additionally, a microdeletion in an individual with CHD was found in the medical literature. Mouse models showed perturbation of the Slit-Robo signalling pathway, causing septation and outflow tract defects and craniofacial anomalies. Two probands had variable facial features consistent with the mouse model. Conclusion Our findings identify Slit-Robo as a significant pathway in human heart development and CHD.